2008
DOI: 10.1177/0269881108100020
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol co-administration moderates 3,4-methylenedioxymethamphetamine effects on human physiology

Abstract: Alcohol is frequently used in combination with 3,4-methylenedioxymethamphetamine (MDMA). Both drugs affect cardiovascular function, hydration and temperature regulation, but may have partly opposing effects. The present study aims to assess the acute physiologic effects of (co-) administration of MDMA and ethanol over time. A four-way, double blind, randomized, crossover, placebo-controlled study in 16 healthy volunteers (9 male and 7 female) between the ages of 18 and 29. MDMA (100 mg) was given orally and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
6
14
0
Order By: Relevance
“…MDMA also affects temperature regulation, generally increasing body temperature. 15 These findings in humans corroborate previous findings in animals. 8,9 Although MDMA-induced temperature increase has received abundant attention in the literature, the mechanism is as yet unclear.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…MDMA also affects temperature regulation, generally increasing body temperature. 15 These findings in humans corroborate previous findings in animals. 8,9 Although MDMA-induced temperature increase has received abundant attention in the literature, the mechanism is as yet unclear.…”
supporting
confidence: 89%
“…[10][11][12][13][14] In a previous report we suggested that the increases in cardiovascular measures and temperature after MDMA administration are mediated by increases in the blood concentrations of both norepinephrine and epinephrine. 15 These findings in humans corroborate previous findings in animals. [16][17][18] Case reports of severe, sometimes fatal, physiologic disturbances after MDMA use, often exacerbated by unfavorable behavior such as vigorous dancing and/or circumstances such as high ambient temperatures, illustrate the relevance of these side effects of MDMA use.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In addition to the EEG data, subjective, neuropsychological and physiological data were acquired, which have already partially been published (Dumont et al 2008, 2009a, b, 2010a, b, c). …”
Section: Methodsmentioning
confidence: 99%
“…Physiological and behavioural studies in humans and rodents have demonstrated an interaction between these two drugs (Mohamed et al, 2009). In humans, ethanol enhances and prolongs the euphoria and feelings of well-being induced by MDMA (Hernández-López et al, 2002), but moderates some of its physiological effects, such as fluid retention and hyperthermia (Dumont et al, 2010). In addition, animal models have demonstrated that the hyperpyretic effect of MDMA is modulated by Ethanol according to the moment of ethanol administration and ambient temperature (Cassel et al, 2004(Cassel et al, , 2005.…”
Section: Mdma and Ethanol Bingesmentioning
confidence: 99%